2020
DOI: 10.1159/000510156
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Outcome after Cochlear Implantation in Children with DFNB7/11 Caused by Pathogenic Variants in <b><i>TMC1</i></b> Gene

Abstract: <b><i>Introduction:</i></b> Non-syndromic hereditary hearing loss is characterized by extreme genetic heterogeneity. So far, more than 100 pathogenic or likely pathogenic variants in <i>TMC1</i> gene have been reported in patients with autosomal recessive hearing loss (HL) DFNB7/11. The prevailing auditory phenotype of individuals with DFNB7/11 is congenital, profound, bilateral HL, but the functional outcome after cochlear implantation (CI) described in the literature is va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
(27 reference statements)
1
5
0
Order By: Relevance
“…Previous work has shown variable auditory outcome in patients with pathogenic biallelic TMC1 variants [ 19 , 21 , 22 , 23 ]. Most reports are small case series with heterogeneous samples, which makes it difficult to assess the full effect of a particular genotype.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work has shown variable auditory outcome in patients with pathogenic biallelic TMC1 variants [ 19 , 21 , 22 , 23 ]. Most reports are small case series with heterogeneous samples, which makes it difficult to assess the full effect of a particular genotype.…”
Section: Discussionmentioning
confidence: 99%
“…Most reports are small case series with heterogeneous samples, which makes it difficult to assess the full effect of a particular genotype. Recent study reported three patients with pathogenic compound heterozygous TMC1 variants demonstrating excellent functional outcome after Cis [ 22 ]. Interestingly, one of the patients in this study was compound heterozygous for the Finnish enriched TMC1 c.1534C>T, p.(Arg512*) variant [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Awaiting development of implantable devices for muscle stimulation, as effective as pacemakers for cardiac arrhythmias [10], implantable stimulators for ventilation supports [11,12] or cochlear implants for hearing loss [13,14], education of sedentary patients to perform home physical exercises could be an effective low-cost alternative during and after hospitalization [15][16][17]. Cardiovascular and ventilation physical rehabilitation protocols of surgical patients are well-established approaches, whose main goal is to reverse muscle weakness [18,19].…”
mentioning
confidence: 99%
“…Besides eventual pharmacological treatment, a home-based physical exercise approach is helpful in counteracting muscle atrophy. Awaiting development of implantable devices for muscle stimulation, as effective as pacemakers for cardiac arrhythmias, 5 implantable stimulators for ventilatory supports, 6,7 or cochlear implants for hearing loss, 8,9 education of sedentary patients to perform home physical exercises could be an effective low-cost alternative during and after hospitalization. [10][11][12] Cardiovascular and respiratory physical rehabilitation protocols of surgical patients are well established approaches, whose main goal is to reverse muscle weakness/atrophy.…”
mentioning
confidence: 99%